Hungarian Monitoring, 24 July 1990 . [Magyar rádiófigyelő], 1990. július 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Overview of the situation in Bulgaria - Work stoppages in Kiev - Differences of opinion between Gorbachev and Shevardnadze - Growing unemployment in Poland - Dissatisfaction in Cuba Domestic Affairs: - Romulus Neagu arrives in Budapest - Accusations against the instigator of the Dunagate case - Six-party talks on the draft local government law - Hungarians working in the FRG - Illegal weapons trade in decommissioned Soviet barracks Economy: - Top list of loss-making enterprises Külpolitika: - Bulgáriai helyzetkép - Munkabeszüntetések Kijevben - Nézetkülönbségek Gorbacsov és Sevardnadze között - Növekvő munkanélküliség Lengyelországban - Elégedetlenség Kubában Belpolitika: - Budapestre érkezett Romulus Neagu - Vádemelés a Dunagate kirobbantója ellen - Hatpárti tárgyalások az önkormányzati törvénytervezetről - Magyarok munkavállalása az NSZK-ban - Illegális fegyverkereskedelem a leszerelt szovjet laktanyáknál Gazdaság: - Veszteséges vállalatok toplistája